Antibiotic Associated Diarrhea in Hospitalized Adult Patien - Marcellus Simadibrata; Lie Khie Chen; Diana Aulia; Ina Sutanto Timan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: Antibiotic associated diarrhea (AAD) occurs from the first initiation until 2 months of the end of antibiotic treatment. The aims of this study were to know the incidence of AAD, Clostridium difficile infectionand other gastrointestinal symptoms in hospitalized adult patients.Method: The study is a cross sectional study. We studied the antibiotic associated diarrhea (AAD), Clostridiumdifficile infection and other gastrointestinal symptoms in patients who were admited in Cipto Mangunkusumo Hospital. Inclusion were male or female, age 18-75 years old, patients started receiving antibiotics maximal 2x 24 hours prior to hospitalization, gave written informed consent.Results: The incidence of AAD was 11.5%. The incidence of Clostridium difficile infection was 15.4%. The upper gastrointestinal symptom was present on 20 (38.5%) patients. Lower abdominal symptom was present on 10 (19.2%) patients.Conclusion: The Incidence of AAD and Clostridium difficile infection were 11.5% and 15.4% respectively.The clinical manifestations of AAD were diarrhea, other upper and lower abdominal symptoms.